2013
DOI: 10.1186/1556-276x-8-547
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology and optical properties of porphyrin/Au and Au/porphyrin/Au systems

Abstract: Porphyrin/Au and Au/porphyrin/Au systems were prepared by vacuum evaporation and vacuum sputtering onto glass substrate. The surface morphology of as-prepared systems and those subjected to annealing at 160°C was studied by optical microscopy, atomic force microscopy, and scanning electron microscopy techniques. Absorption and luminescence spectra of as-prepared and annealed samples were measured. Annealing leads to disintegration of the initially continuous gold layer and formation of gold nanoclusters. An am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Also, it appears that the difference in size of the prepared particles is hard to correlate with macroscopic properties of ILs, such as viscosity or surface tension [95]. The nanoparticles prepared as solutions may be used in different applications on the basis of surface grafting on polymer substrates [100][101][102][103], mostly used in tissue engineering [104][105][106][107] or for construction of antibacterial substrates [108].…”
Section: Vacuum Sputteringmentioning
confidence: 99%
“…Also, it appears that the difference in size of the prepared particles is hard to correlate with macroscopic properties of ILs, such as viscosity or surface tension [95]. The nanoparticles prepared as solutions may be used in different applications on the basis of surface grafting on polymer substrates [100][101][102][103], mostly used in tissue engineering [104][105][106][107] or for construction of antibacterial substrates [108].…”
Section: Vacuum Sputteringmentioning
confidence: 99%
“…Such undulation(s) in surface is suggestive toward temperature induced agglomerations (as apparent from formation of globules), that has led to opening up of SWCNTs surface to the analyte, resulting in high degree of adsorption at SWCNTs sidewalls and interstitials . Kalachyova et al have also reported such bulges in TPP films after annealing at 160 °C. Line profiles further reflected gradual decrease in average device diameter with increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Sensing of mercury, in particular, is important because mercury is harmful to both human health and the environment, as it is highly soluble in water and even at low concentrations is known to adversely affect the endocrine, nervous and excretory systems [ 96 ]. Furthermore, existing detection methods are time consuming and require sophisticated instruments [ 97 99 ]. The platform developed by Wu et al .…”
Section: Quantitative Luminescence-based Sensingmentioning
confidence: 99%